The prejudice and the virtue. The re-education of the antisocial child in the pages of the “Rivista di Pedagogia Correttiva” (1907-1915) - Giachery, Gianluca (Rivista di Storia dell’Educazione, 2023)
In the European pedagogical culture, between the end of the Nineteenth century and the first decade of the Twentieth century, particular attention is paid to a category of children and adolescents who are called “corrigendi”. They are poor children, almost always from large families and deprived, left to their own and in a daily idleness. Medical Doctors, pedagogists, jurists and criminal anthropologists – in the wake of the pioneering works of Pinel, Itard and Séguin – agree on the need for the education of these children, who must be “corrected” in character and moral action. Since the Twenties of the Twentieth century, this category, further defined, described and identified, will be replaced by the other, more extensive but also more intrusive, of “antisocial and deviant boys”. In this perspective, the material contained in the “Rivista di Pedagogia Correttiva”, directed by Mario Carrara and Camillo Tovo, published between 1907 and 1915, allows to identify the genealogy of this process in the attention given by pedagogists, medical doctors and jurists on the need to “correct” any kind of deviant manifestation of the child and adolescent. This is the pivot of a reflection that has, since the second half of the Twentieth century, a specific place in the concepts and practices of “rehabilitation” and “occupational therapy”.